Convex analysis and nonlinear geometric elliptic equations - Bakelman, Ilya J. (Springer-Verlag, 1994)
This graduate-level text examines the areas of convex functions and bodies, global geometric problems and nonlinear elliptic boundary value problems, emphasizing Monge-Ampere equations.